Psychological counseling and nursing interventions with Traditional Chinese Medicine characteristics for a patient with cluster headache (心理辅导护理联合中医特色疗法治疗丛集性头痛1例的护理体会) - LIU Caidan (刘才丹); YU Yanlan (余艳兰); ZHOU Yunbo (周运波); LUO Huanwen (罗焕文) (中西医结合护理)
This paper summarized the experience of psychological counseling and nursing interventions with Traditional Chinese Medicine (TCM) characteristics for a patient with cluster headache. Based on the precise nursing assessment and TCM syndrome differentiation, nursing interventions with TCM characteristics including scraping therapy and moxibustion were carried out. Nurses had paid attention to the mental health of the patient and provided psychological care to the patient and family members. (本文总结1例采用心理辅导护理联合中医特色疗法治疗丛集性头痛的护理经验。通过精准的护理评估, 明确护理目标, 并基于中医基础理论辨证施护, 采取刮痧、艾灸等中医特色疗法, 同时积极关注患者心理问题, 为患者及家属提供良好的心理疏导, 进而达到身心同治的效果。)